Non-cultural detection of rectal and pharyngeal gonorrhoea by the Gen-Probe PACE 2 assay. Issue 1 (February 1997) - Young, H; Anderson, J; Moyes, A; McMillan, A
Abstract : OBJECTIVE: To assess the sensitivity and specificity of the Gen-Probe PACE 2 assay, which uses a chemiluminescent labelled single-stranded DNA probe to detect gonococcal ribosomal RNA (rRNA), for the non-cultural detection of rectal and pharyngeal gonorrhoea in homosexual men. SUBJECTS: 161 homosexual men attending the Department of Genitourinary Medicine, Edinburgh Royal Infirmary during the latter half of 1995 and the first quarter of 1996. METHODS: Duplicate rectal and pharyngeal swabs were collected for culture on modified New York City (MNYC) medium and detection of gonococcal nucleic acid by the Gen-Probe assay. Repeatedly reactive Gen-Probe specimens from culture negative patients were also tested by the Gen-Probe competition assay (PCA). RESULTS: Of the 161 patients, 23 (14.3%) gave a positive culture at one or both sites (rectum 10, throat 8, rectum and throat 5) compared with 28 (16.7%) who gave a positive Gen-Probe result at one or both sites (rectum 9, throat 11, rectum and throat 8). After resolution of discrepant results by PCA the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of Gen-Probe was 94.1%, 100%, 100% and 99.3% for rectal specimens while the corresponding values for pharyngeal specimens were 86.4%, 100%, 100%, and 97.9%. The sensitivity and NPV of rectal culture were 88.2% and 98.6% while the corresponding values for pharyngeal culture were 59% and 93.9%. Gen-Probe was significantly more sensitive than throat culture (p < 0.05) but not rectal culture (p > 0.2). The average Relative Light Units (RLU) value for the cut-off was 386 (range 351-450) while the average for a positive result was 20306 (range 403-110104): this was, however, significantly higher (p = 0.019) in rectal specimens 31325 (range 1705-110104) than in throat specimens 10447 (range 403-15633). CONCLUSIONS: Gen-Probe PACE 2 assay is a sensitive and specific method for the detection of rectal and pharyngeal gonorrhoea. As the Gen-Probe assay may detect nucleic acid from non viable gonococci the clinical significance of a probe positive culture negative specimen from a patient without culture evidence of gonorrhoea at another site is uncertain and requires further consideration. Nevertheless a positive result does indicate exposure to infection and could be important in ensuring appropriate partner notification action. If non-cultural methods are used to screen for gonococcal infection cultures should be obtained from patients with positive results in order that the antibiotic susceptibility and molecular epidemiology of the gonococcal population can be monitored.